Competitividad de las exportaciones de carne vacuna de Argentina durante el período 1996 - 2007: Análisis comparativo con Brasil - Marta Susana Picardi; Josefina Blanco; Julieta Perrier (Atlantic Review of Economics, 2011)
– The industry of the bovine meat is important in the economy of the Argentine Republic for being an activity with old tradition, has a world-wide recognition of quality and it constitutes a source of currency entrance by exports. The sector counts with comparative advantages for the production because the country has a great variety of climates and had abundant natural resources but, it had a low advantage of these comparative and competitive potentials advantages in spite of constituting an activity that was developed in parallel with the history of the country. Brazil on the other hand is like a great strategist to take advantage of the own ones, and in a few years it obtained a position superior to the one of Argentina although it has not been able until now to obtainng the quality of the meats of Argentine Pampas. With the aim to demonstrate the evolution in the gains of competitiveness of Brazil respect to Argentina we use indicators recognized in the economic bibliography. With respect to the determinants of this process, an analysis begins in this work that will have to be deepened in a later stage. -
Keywords: F1; 330